Thermoelectric-Based Low-Cost Water Chiller via Peltier-Plates - Manap A.; Mahalingam S.; Rabeya R.; Afandi N.M.; Nkaita S.B.; Om N.I. (Penerbit Akademia Baru, 2023)
This study aims to design and build a water-chilling device for strawberry irrigation in low-land areas in Malaysia. Strawberries possess better growth in a chilled environment. On that note, a chilling thermoelectric device known as the Peltier plate has been used in this project, which follows an open-cycle system. This process is cost-effective and more convenient than the other methods used for strawberry plantation, such as providing an air-conditioner, which is costly, and using a sprinkler, which may rot the strawberries in wet conditions. Therefore, we propose a low-cost chilling device to chill the water with low-temperature water to be applied in strawberry plants. The plant treated with the water chiller showed better growth with 12 cm of height. The thermoelectric effect has been adopted in this study as the source of chilling since it reduces the temperature on one side and increases it on the other side. The heat is to be discharged using two fans to increase the difference in temperature between the two sides of the thermoelectric device. It involved the Peltier effect, which generates the voltage from the power source to heat/temperature differentials. The obtained result revealed a temperature difference of 5.7 C between the water-in (27 C) and water-out (21.3 C), considered the optimum temperature for strawberries to survive well. 2022, Journal of Advanced Research in Fluid Mechanics and Thermal Sciences. All Rights Reserved.